Kesuksesan Muslimah Pelaku UMKM: Peran Dimensi Entrepreneurial Orientation - Supriyanto, Agus; Permatasari, Ririt Dwiputri; Prihastuti, Asepma Hygi; Saputra, Tommy; Bora, M. Ansyar (Universitas Islam Negeri Sunan Kudus, 2022)
The purpose of this study was to determine the factors that support the success of Muslim women in running a business seen from the dimensions of entrepreneurial orientation. Respondents in the study were 105 Muslim SMEs who run businesses in Kudus Regency. The sampling technique uses Simple Random Sampling with the Convenience Sampling method. The data analysis technique uses Structural Equation Modeling with the help of AMOS 25.0. The results of the study indicate that there is a significant influence between innovation, risk taking, proactivity, competitive aggressiveness and autonomy on the birth of Muslim women as MSME actors. All dimensions of entrepreneurial orientation are proof that to achieve success in running a business, a business actor needs to implement the dimensions of entrepreneurial orientation. The autonomy dimension gets the highest average answer, it is important to pay attention that the delegation of authority and responsibility to employees to make accidental decisions. The managerial implication of this research is that SMEs need to pay attention to the dimensions of entrepreneurial orientation because it will have an impact on improving business performance.